Effect of village funds and other variables on economic growth of Central Java Province 2015–2018 - Rizka Amalia Farentina (Economic Research Center, the Indonesian Institute of Sciences (P2E-LIPI), 2022)
The Economic growth of Central Java Province from 2015 to 2018 experienced a slowdown compared to other provinces in Java. One of the main focuses on improving the economy is fiscal decentralization which is manifested in the form of village funds. This is in line with one of nine development priorities for the next five years agendas, or so- called Nawacita, namely to develop Indonesia from the periphery by strengthening regions and villages within the framework of a unitary state. The village funds data from the Ministry of Finance shows that Central Java Province receives the largest village funds each year, but this does not necessarily increase economic growth in the recipient districts. In addition to the economic growth policy, the government also plans through investment and government spending. The purposes of this study are to determine the effectiveness of the village fund budget and the effect of the realization of village funds, capital expenditure, goods and services expenditure, and the level of open unemployment on economic growth. The method used in this study is the panel data regression analysis method with the research locus of 29 districts receiving village funds in Central Java Province from 2015 to 2018. The results of the study using the selected panel data regression model that is the Fixed Effect Model FGLS SUR show that all independent variables influence significantly to economic growth (GRDP). The variable realization of village funds and goods and services expenditure has a significant positive effect, while the variable realization of capital expenditure and the variable open unemployment has a significant negative effect on economic growth (GRDP).